Design improvement of outer-rotor hybrid excitation flux switching motor for in-wheel drive electric vehicle - Wan Husin, Wan Norhashimah (2014)
Due to in-wheel motors definite benefits of great controllability for each self-reliant wheel as well as the convenience of more space of cabin due to conventional mechanical transmission and differential gears are removed, more study and research of in-wheel motors used in pure electric vehicles (EVs) propulsion systems have attracted and involved great attention lately. Furthermore, more series batteries can be mounted to gain the distance of driving. The main necessities are to have high torque density and efficiency, since the motors are installed directly to the wheel. Because of high torque possibility is required; a design of outer-rotor hybrid excitation flux switching motor for in-wheel drive electric vehicle is suggested in this project. The suggested motor consists of twelve (12) slots of stator poles, and ten (10) rotor poles. All these active parts are placed on the stator. Secondarily, it has a steady rotor assembly which only contains a single piece of rotor and has a wide range flux control abilities. Under some design restrictions and specifications for the target electric vehicle drive applications, the performance of the suggested machine on the initial design and improved design are analyzed based on 2-D finite element analysis (FEA). The performance of the improved design motor shows that the maximum torque achieved is 241.7921 Nm which is 72.61 % of the target performance, whereas the maximum power has achieved 143.47 kW which is greater than the target value. Therefore, by extra design optimization it is estimated that the motor will successfully reach the target performance.